Analisis Homologi Fragmen DNA CVPDr dari Jeruk Kinkit Trophasia trifolia Menggunakan BLAST Protein Dan BLAST Nukleotida - BAGUS, WHISNU IDA; WIRAWAN, I GEDE PUTU; ADIARTAYASA, I WAYAN (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2019)
Homology Analysis Of CVPDr DNA Fragment from 13 Citrus Variety in Bali Using Nucleotide Blast And Protein Blast CVPDr  from Trhiphasia trifolia is predicted to have to increase resistance from CVPD, but the mechanism of this DNA is still largely unknown. The first step of DNA analyzing is by using homology with Nucleotide and Protein BLAST. BLAST can identify, similarity search, and predict the function of DNA. The goal of this research is to compare CVPDr  DNA fragment from T. Trifolia with sequences from NCBI Genbank and finding it’s significant homology using nucleotide BLAST and protein BLAST. Nucleotide BLAST result shows that “DNA Citrus nobilis cultivar Tabanan citrus vein phloem degeneration r protein (CVPDr) gene, partial cds” have the highest homologs, the other sequences that’s shown by BLAST does not have high enough similarity to be homologus. Protein BLAST show “citrus vein phloem degeneration r protein [Citrus nobilis]” have the highest homologs, but even if the other BLAST result have percentage of similarity lower than 55% there are still possibility of structural homolog because the E value is lower than 0.01.